1976 Democratic National Convention - - Women Delegations and Alternates (1976)
This document presents a state-by-state breakdown of women delegates and alternates at the 1976 Democratic National Convention. It lists the total number of delegates and alternates for each state and territory, the number of women in each category, and the percentage of women represented. Overall, the totals show 3,075 delegates, of whom 1,036 (34%) were women, and 1,902 alternates, of whom 740 (39%) were women. Notes indicate that some states with fewer than 16 delegates could select 16 individuals to cast their votes, and that credentials challenges resulted in additional delegates or fractional votes in certain states. The report was issued by the Democratic National Committee's Office of Women's Activities.